Beta-thromboglobulin as a marker of perioperative myocardial infarction in patients undergoing coronary artery bypass grafting following aspirin discontinuation. (December 2014) - Plicner, Dariusz; Ziętkiewicz, Mirosław; Mazur, Piotr; Stąpor, Renata; Sadowski, Jerzy; Undas, Anetta
Abstract Perioperative myocardial infarction (PMI) following coronary artery bypass grafting (CABG) is associated with significant morbidity and mortality. The aim of this study was to assess platelet activation and oxidative stress in the setting of PMI in patients undergoing CABG. We studied 108 consecutive patients who stopped taking low-dose aspirin 7–10 days prior to elective isolated on- or off-pump CABG. β-thromboglobulin (β-TG), thromboxane B2 (TXB2) and 8-iso-prostaglandin F2α (8-iso-PGF2α), a marker of oxidative stress, were measured at the baseline and 5–7 days postoperatively. Aspirin (150 mg/d) was administered every morning since 12 hours after CABG. Mean baseline β-TG was 58.5 ± 10.3 IU/ml, TXB2 was 143.6 ± 28.5 ng/ml and 8-iso-PGF2α was 355.2 ± 40.7 pg/ml. Postoperatively, after administration of 4–6 doses of aspirin, β-TG increased by 16.7% and 8-iso-PGF2α increased by 17.2% 5–7 days after surgery (p = 0.005 and p < 0.001, respectively). TXB2 decreased by 99.7% to 410.3 ± 52.1 pg/ml (p < 0.001). Nine patients (8.3%) developed PMI. Baseline β-TG and TXB2, together with postoperative β-TG and 8-iso-PGF2α were higher in PMI patients than in the remaining subjects (all, p < 0.05). Multivariate analysis showed that baseline β-TG (OR: 1.28; 95% CI: 1.05–1.57, p = 0.015) was the only independent predictor of PMI. In conclusion, we demonstrated that increased platelet activation and thromboxane production, observed in patients not taking aspirin till the day of CABG, contribute to the occurrence of PMI in early postoperative period.